TELAAH ARSITEKTUR HERITAGE TRAIL KOTA ISTANBUL, TURKI - Ari Widyati Purwantiasning; Saeful Bahri (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2023)
This paper is a literature and precedent study examining the heritage trail of the City of Istanbul, Turkey. Istanbul, Turkey, was chosen as the object of the precedent study because the city is rich in history and Islamic civilization. As the title implies, this study also aims to reveal how the heritage trail is applied as a tourism of Islamic culture and history. As a reference, a guide on the heritage trail is used to review each trail presented for analysis. Four heritage trails in the City of Istanbul have been selected to represent all existing heritage trails. These four trails are the Istanbul Introduction Walk, the Istanbul Old CLineline, the Mosques of Istanbul Lane, and the Old European Quarter line. Four heritage trails were chosen as a representation of the many heritage trails in Istanbul, Turkey, and are four paths that have spatial meaning both spatially and in terms of building figures that can represent all heritage trails of Istanbul, Turkey. The study is carried out on the study of precedents by applying narratively the method of literature and precedent study. Data was collected through field observation techniques, observations, and experiences of the architectural space of the City of Istanbul. Direct description of objects is also done by doing the experience of architectural space on each object discussed in this precedent study. The results of this study are intended as a discourse and additional insight for all circles, both academics and the broader community, so that they better understand the existence of cultural heritage around it. With the guidance of the heritage trail, the study is carried out based on existing principles, looking at the grouping of buildings on each path presented based on the year of civilization, architectural style, history, and supporting elements.